Suicide prevention campaigns and their reception by young university students - Tondo, Rômulo Oliveira; Piedras, Elisa Reinhardt; Magalhães, Pedro Vieira da Silva (MATRIZes, 2024)
Addressing communication and health, this research aims to analyze suicide prevention campaigns and their reception by young university students. This qualitative methodology involved document analysis (campaigns from 23 organizations) and successive semi-structured interviews (with 12 youths) and is characterized as a study of advertising reception. Results show that the campaigns scarcely impact the studied youths and that their communication often addresses the promotion of mental health instead of suicide prevention, reinforcing taboos and failing to fulfill, as pointed out by the public in the reception practices, the expected function of informing people about means of helping and assisting imminent suicides.